TikTok as a Resource for Fertility Information and Support: A Patient Survey - Abirami Kirubarajan; Seoyeon Han; Priyanka Patel; Amanda Black; Sony Sierra (Journal of Family and Reproductive Health)
Objective: TikTok is a rapidly growing social media platform with over 800 million users worldwide. Many patients access fertility-related content across social media platforms, however, this has never been studied related to TikTok. This study aimed to describe patient perspectives and experiences using TikTok for fertility-related content. Materials and methods: We conducted a cross-sectional web-based survey from April 1st 2023 to October 1st 2023 at a large fertility center in Toronto, Canada. Patients were eligible for inclusion if they self-identified that they use TikTok for fertility-related content and had pursued any form of fertility care. Results of the survey were described with descriptive statistics and thematic analysis. Results: A total of 23 patients with a mean age of 36.74±6.67 years participated in the online survey. Fertility-related TikTok content included lived experiences of fertility journeys descriptions of fertility treatments or procedures, live-streaming of fertility treatments or procedures, interactive questions and answers, and educational videos. Creators of fertility-related TikTok content include patients undergoing fertility treatments, physicians, naturopaths, counselors, and patient advocates. The most common reasons for liking TikTok for fertility content included empathy or shared experiences, stress relief, and self-education. Reasons for disliking TikTok for fertility information included misinformation, commercialization or advertisements, and negative emotions of stress, anxiety, or emotional upset. Misconceptions seen on TikTok included misinformation about complications and success rates for assisted reproductive therapy, as well as nutritional advice. Conclusion: Fertility providers should have a growing awareness of information available on TikTok for patients accessing fertility care and assisted reproductive technology.